Absolute Freedom of Speech and Social Media: Deconstructing the Argument of Individual Self-Realization - Bresolin, Keberson (Daimon Revista Internacional de Filosofia, 2024)
El artículo cuestiona la concepción absoluta de la libertad de expresión como medio incondicional para la autorrealización individual. Inicialmente, se discute la posición de Scanlon y Redish, revelando las vulnerabilidades inherentes a sus argumentos. A continuación, se argumenta en contra de la visión de una libertad de expresión ilimitada como esencial para la autorrealización. Finalmente, aun aceptando la premisa de la autorrealización como axioma, las redes sociales no se calificarían como arenas adecuadas para su efectuación, dada su incapacidad para replicar las características fundamentales de una esfera pública que favorezca el debate abierto, plural y racional. The paper challenges the absolute conception of freedom of speech as an unconditional means for individual self-realization. Firstly, it discusses the positions of Scanlon and Redish, revealing the inherent vulnerabilities in their arguments. Subsequently, it argues against the view of unlimited freedom of speech as fundamental to self-realization. Finally, even if one were to accept the premise of self-realization as an axiom, social media would not qualify as suitable arenas for its actualization, given their inability to replicate the fundamental characteristics of a public sphere that favors open, plural, and rational debate. Keywords: self-realization, autonomy, Scanlon, social media, public sphere, Habermas.